2019
DOI: 10.1002/em.22334
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an Aneugenic Mechanism of Action for Micronucleus Induction by Black Cohosh Extract

Abstract: Black cohosh extract (BCE) is a popular botanical dietary supplement marketed to relieve symptoms of various gynecological ailments. Studies conducted by the National Toxicology Program (NTP) showed that BCE induces micronucleated erythrocytes in female rats and mice. Subsequently, the NTP showed that a variety of BCEs, including the sample that induced micronuclei (MN) in vivo (“NTP BCE”) had a similar effect in human TK6 cells. Further testing with the MultiFlow® DNA Damage Assay revealed that TK6 cells expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…However, DNA damage can affect only one strand (single strand breaks, SSBs), without leading to the formation of micronuclei. Additionally, the presence of micronuclei may be related to an aneugenic effect, that is, a disturbance in the cell division process, which may be related to changes in the division apparatus, leading to the isolation of entire chromosomes (BERNACKI et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…However, DNA damage can affect only one strand (single strand breaks, SSBs), without leading to the formation of micronuclei. Additionally, the presence of micronuclei may be related to an aneugenic effect, that is, a disturbance in the cell division process, which may be related to changes in the division apparatus, leading to the isolation of entire chromosomes (BERNACKI et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…MN may be formed via two basic mechanisms: whole chromosome loss (aneugenicity), or failure of an acentric, broken chromosome (clastogenicity) to migrate to a spindle pole during mitosis. The DNTP BC extract was shown to induce MN through destabilization of microtubules, resulting in whole chromosome loss during mitosis (Bernacki et al, 2019). Additional studies have provided some evidence that the DNTP BC extract may have transient DNA‐damaging effects as well (Seo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that CIT increases MN formation and induces apoptosis (Sabharwal et al, 2015). Formation of MN could be attributed to chromosomal breaks, indicating clastogeny, and by loss of chromosomes by the effects of aneugenic agents (Bernacki et al, 2019). Research findings indicated that CIT induces BC in the hepatocytes that may be an indication of cytokinesis failures at the end of cell division, and cells with condensed chromatin are signs of apoptosis (karyorrhexis and karyolysis) as well as picnoses (Sabharwal et al, 2015).…”
Section: Discussionmentioning
confidence: 99%